Anticonvulsant activity of bioflavonoid gossypin - Rasilingam, Duraisami; Duraisamy, Srinivasan; Subramanian, Ramaswamy (Bangladesh Journal of Pharmacology, 2008)
The anticonvulsant activity of gossypin was investigated by studying the effects on seizures induced by pentelentetrazole, strychnine and maximal electroshock convulsive methods in mice. Gossypin (10 and 20 mg/kg) significantly reduced the duration of convulsion in tonic seizure induced by pentelenetetrazole (95 mg/kg, intraperitoneally). Gossypin (20 mg/kg p.o) significantly reduced the tonic extensor convulsion induced by strychnine and maximum electroshock-induced convulsions. The data obtained suggest that gossypin have anticonvulsant property and may probably be affecting both GABA aminergic and glycine inhibitory mechanism.